Combining static and dynamic analysis for the reverse engineering of web applications - Silva, Carlos Eduardo (2013)
Software has become so complex that it is increasingly hard to have a complete understanding of how a particular system will behave. Web applications, their user interfaces in particular, are built with a wide variety of technologies making them particularly hard to debug and maintain. Reverse engineering techniques, either through static analysis of the code or dynamic analysis of the running application, can be used to help gain this understanding. Each type of technique has its limitations. With static analysis it is difficult to have good coverage of highly dynamic applications, while dynamic analysis faces problems with guaranteeing that generated models fully capture the behavior of the system. This paper proposes a new hybrid approach for the reverse engineering of web applications' user interfaces. The approach combines dynamic analyzes of the application at runtime, with static analyzes of the source code of the event handlers found during interaction. Information derived from the source code is both directly added to the generated models, and used to guide the dynamic analysis.